Evaluación de una Estrategia Colaborativa: un estudio de caso en el sector del vino de Oporto - Moreira, António Carrizo; Moutinho, Victor Ferreira; Pereira, José da Costa (Review of Business Management, 2013)
The rapid and all-encompassing changes in regional and world wine markets have stimulated us to carry out this study. Accordingly, based on the competitiveness of an important Port wine producer in Portugal, this article analyzes a strategic alliance between this company and another important multinational one that is present in many different worldwide distribution markets. Basically, the article seeks to understand, on the one side, the impact of a strategic alliance on a small Port wine producer when becoming involved with a multinational company, and, on the other hand, to identify differences, before and after the alliance, to the markets where the small company was made present. This work is centered on a case study and involves the use of econometrics methodologies that analyze panel data, in order to grasp differences of strategic pre- and post-alliance actions. The conclusions are important, since they allow one to compare, on one hand, difference between the company´s performance over two different time horizons. On the other hand, econometrics methods are robust, since they allow one to come to relational conclusions, keeping the case study in mind.